The prospects of international trade regulation : from fragmentat ion to coherence - Cottier, Thomas; Delimatsis, Panagiotis (Cambridge ; New York : Cambridge University Press, 2011)
"For a long time, the GATT led a life of its own as a self-contained regime. The evolution from tariff to non-tariff barriers brought about increasing overlaps with other regulatory areas. WTO rules increasingl y interface with other areas of law and policy, including environmental protection, agricultural policies, labour standards, investment, human rights and regional integration. Against this backdrop, this book exam ines fragmentation in international trade regulation across a wide arra y of regulatory fields. To this end, it uses a conceptually coherent th eoretical framework which is based on the effort to bring about greater coherence among different policy goals and fields, and thus to embed t he multilateral trading system within the broader framework of internat ional economics, law and relations. It will appeal to those interested in a forward-looking discussion of the most pressing issues of the inte rnational trade agenda"--
Machine generated contents note: 1. The fragmentation versus coheren ce discourse in international law and its relevance for trade regulatio n Thomas Cottier, Panagiotis Delimatsis and Katja Gehne; Part I. Consti tutional Issues in International Trade Regulation: 2. The constitutiona lisation of international trade law Klaus Armingeon, Karolina Milewicz, Simone Peter and Anne Peters; 3. Reflections on modes of decision-maki ng in the WTO Yves Bonzon, Manfred Elsig, Marina Foltea, Thomas Messerl i and Andreas Ziegler; 4. Regionalism - moving from fragmentation towar ds coherence Richard Baldwin and Theresa Carpenter; Part II. Reforming Specific Areas of Trade Regulation: 5. Reframing sustainable agricultur e Philipp Aerni, Baris Karapinar and Christian Ha;berli; 6. Energy in W TO law and policy Thomas Cottier, Garba Malumfashi, Sofya Matteotti-Ber kutova, Olga Nartova, Joèelle De Se;pibus and Sadeq Z. Bigdeli; 7. Deve loping trade rules for services: a case of fragmented coherence? Panagi otis Delimatsis, Nicolas Diebold, Marti;n Molinuevo, Marion Panizzon an d Pierre Sauve;; 8. Challenges of biotechnology in international trade regulation Susette Biber-Klemm, Michael Burkard, Thomas Cottier, Sufian Jusoh and Michelangelo Temmerman; Part III. 'Trade and ...' Linkages: 9. A call for a WTO ministerial decision on trade and human rights Barn ali Choudhury, Katja Gehne, Simone Heri, Franziska Humbert, Christine K aufmann and Krista Nadakavukaren Schefer; 10. The protection and promot ion of cultural diversity in a digital networked environment - mapping possible advances to coherence Mira Burri, Christoph Beat Graber and Th omas Steiner; 11. Development and stability in the nexus between trade and finance Ernst Baltensperger and Nils Herger; 12. International inve stment framework - the regulatory fragmentation challenge in a changing world economy Bertram Boie, Julien Chaisse and Philippe Gugler; 13. Lo w-income countries and commodity price volatility Hannah Bargawi, Elva Bova, Benno Ferrarini and Susan Newman.
Includes bibliographical references and index.
Keywords: Foreign trade regulation; LAW / International